Juvenile Hormone-Sensitive Ribosomal Activity Enhances Viral Replication in Aedes aegypti - Zuo-Kun Shi (American Society for Microbiology, 2021)
Most flaviviruses are transmitted between hosts by arthropod vectors such as mosquitoes. Since therapeutics or vaccines are lacking for most mosquito-borne diseases, reducing the mosquito vector competence is an effective way to decrease disease burden.